Investigation of the presence and persistence of bacteria in seawater and oysters from an aquaculture farm in Rehoboth Bay, Delaware - Kelvin F. Ofori; Ali Parsaeimehr; Gulnihal Ozbay (Microbiology Spectrum)
ABSTRACT The filter-feeding nature of oysters, anthropogenic activities, and increasing agriculture in Delaware compromise the microbial safety of Eastern oysters from local aquaculture farms. From July to October 2023, we evaluated the presence and persistence of eight bacteria in seawater and oysters produced from off-bottom and bottom cultures at Sally Cove, an aquaculture farm within Rehoboth Bay in Delaware. A control site within Sally Cove, which was without oyster cultures, was also included in the study. Seawater temperature, salinity, pH, and dissolved oxygen were measured in situ during sampling. Molecular confirmation with PCR and qPCR showed that Vibrio parahaemolyticus, Shiga-toxin-producing Escherichia coli, Salmonella enterica, Staphylococcus aureus, Pseudomonas aeruginosa, and Clostridium spp. were present and persisted in seawater and oyster samples from both cultures at Sally Cove and in off-bottom and bottom seawater samples from the control site throughout the study. Shigella spp. and Listeria monocytogenes were consistently found in seawater and oyster samples from July to September. However, Shigella spp. was only detected in samples from the bottom cultures, whereas L. monocytogenes was undetectable in all samples from both cultures in October. The observed temperature, salinity, pH, and dissolved oxygen levels across the study period were in the range of 15.30–29.67°C, 29.33–31.87 ppt, 7.25–7.95, and 3.79–8.10 mg/L, respectively, and comparable with the conditions suitable for the growth and survival of these bacteria. These findings suggest that consuming raw oysters from Sally Cove poses contamination risks from several bacteria, especially in the summer months.IMPORTANCEAlthough studies have evaluated bacterial contamination in seawater and oysters within the Delaware Inland Bays and nearby areas, the focus has primarily been on Vibrio species. However, other bacteria have been found in seawater and seafood at various locations and could potentially occur in oysters produced from aquaculture farms within the Delaware Inland Bays. Sally Cove is an oyster aquaculture farm that produces Eastern oysters (Crassostrea virginica) for consumption in Delaware using both off-bottom and bottom culturing methods. The risk of bacterial contamination from consuming raw oysters from this farm is unknown. This paper shows the presence and persistence of several bacteria, including those associated with waste, in seawater and oysters at the farm. The findings can inform consumers about the contamination risks from consuming raw oysters produced at the farm.